Meta-Analysis: The Effect of The Problem-Based Learning Model on Mathematical Reflective Thinking Ability - Yanto, Bagus; Sri Hastuti Noer; Agung Putra Wijaya (Universitas Pendidikan Ganesha, 2025)
Until now, there have been many studies conducted on mathematical reflective thinking skills presented using problem-based learning models. This study aims to analyze published research on the effectiveness of problem-based learning models on mathematical reflective thinking skills. The method used is meta-analysis. The data analyzed were 8 journal articles that were used to determine the effect size. Data collection was carried out using a variable coding sheet as a coding instrument. The collected data were then analyzed using meta-analytic statistical techniques. The results of the analysis showed that the average effect size of the 8 articles was 2.63, which was included in the high effect size category. Of the 8 articles analyzed, 6 articles (75%) showed a high effect size category, while 2 articles (25%) showed a medium effect size category. The article with the highest effect size, which reached 5.29, shows that the problem-based learning model can provide a very significant increase in students' mathematical reflective thinking skills in learning mathematics.